Virulence function of the Ustilago maydis sterol carrier protein 2. Issue 2 (13th June 2018) - Krombach, Sina; Reissmann, Stefanie; Kreibich, Saskia; Bochen, Florian; Kahmann, Regine
Summary: The peroxisomal sterol carrier protein 2 (Scp2) of the biotrophic maize pathogen Ustilago maydis was detected in apoplastic fluid, suggesting that it might function as a secreted effector protein. Here we analyze the role of the scp2 gene during plant colonization. We used reverse genetics approaches to delete the scp2 gene, determined stress sensitivity and fatty acid utilization of mutants, demonstrated secretion of Scp2, used quantitative reverse transcription polymerase chain reaction for expression analysis and expressed GFP‐Scp2 fusion proteins for protein localization. scp2 mutants were strongly attenuated in virulence and this defect manifested itself during penetration. Scp2 localized to peroxisomes and peroxisomal targeting was necessary for its virulence function. Deletion of scp2 in U. maydis interfered neither with growth nor with peroxisomal β‐oxidation. Conventionally secreted Scp2 protein could not rescue the virulence defect. scp2 mutants displayed an altered localization of peroxisomes. Our results show a virulence function for Scp2 during penetration that is probably carried out by Scp2 in peroxisomes. We speculate that Scp2 affects the lipid composition of membranes and in this way ensures the even cellular distribution of peroxisomes. Abstract : See also the Commentary on this article byRedkar & Di Pietro, 220 : 353–356 .